Analysis Of Islamic Corporate Social Responsibility (Icsr) On Financial Performance In Sharia Commercial Banks In Indonesia For The Period 2020-2023 - Fransiska, Silvia; Nasution, Juliana; Anggraini, Tuti (UNIVERSITAS PAKUAN, 2024)
Islamic Corporate Social Responsibility (ICSR) is an idea that combines sharia principles in the action of corporate social obligations. This study aims to describe and examine the impact of Islamic Corporate Social Responsibility (ICSR) on financial performance projected using the Return On Equity (ROE) indicator in Islamic commercial banks. The research strategy used was panel regression analysis with the help of IBM Statistical Package for Social Sciences (SPSS) program version 24. The results showed that there was no significant positive influence between ICSR and financial performance at Islamic Commercial Banks in Indonesia. This indicates that the ICSR practices implemented by these banks have not contributed significantly to the achievement of their financial performance. This finding is consistent with sharia principles that emphasize the importance of justice, togetherness, and sustainability in business activities. This study contributes to the understanding of the relationship between ICSR and financial performance in the context of Islamic banking in Indonesia. The practical implication of the findings is that Islamic banks can gain long-term benefits by implementing ICSR practices that are consistent with sharia principles, not only from a moral and social perspective, but also from a financial perspective.